Ecology-relevant bacteria drive the evolution of host antimicrobial peptides in Drosophila. - Hanson, M.A.; Grollmus, L.; Lemaitre, B. (Science, 2023)
Antimicrobial peptides are host-encoded immune effectors that combat pathogens and shape the microbiome in plants and animals. However, little is known about how the host antimicrobial peptide repertoire is adapted to its microbiome. Here, we characterized the function and evolution of the Diptericin antimicrobial peptide family of Diptera. Using mutations affecting the two Diptericins (Dpt) of Drosophila melanogaster, we reveal the specific role of DptA for the pathogen Providencia rettgeri and DptB for the gut mutualist Acetobacter. The presence of DptA- or DptB-like genes across Diptera correlates with the presence of Providencia and Acetobacter in their environment. Moreover, DptA- and DptB-like sequences predict host resistance against infection by these bacteria across the genus Drosophila. Our study explains the evolutionary logic behind the bursts of rapid evolution of an antimicrobial peptide family and reveals how the host immune repertoire adapts to changing microbial environments.